2006
DOI: 10.1007/s11255-006-9144-z
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel density and regulators of angiogenesis in malignant and nonmalignant prostate tissue

Abstract: The aim of this study was to investigate the relationship between microvessel density (MVD), positive and negative angiogenic factors, and established prognostic factors in prostate cancer (PC), and, to clarify the effect of angiogenic factors to angiogenesis. The vascularization of neoplastic, non-neoplastic prostate tissue was determined by CD34 immunostaining. Angiogenetic mediators VEGF, bFGF, TSP-1, and p53 were studied by immunohistochemistry. Neovascularization and p53, VEGF, and TSP-1 expressions of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
(48 reference statements)
2
14
2
Order By: Relevance
“…Most analyzed parameters were higher within normal glandular prostatic tissue (MVC, MVA, vessel lumen), whereas MVAF, vessel wall, and vessel perimeters were not significantly different. These findings using the large representative areas contradict most previously published data with the hot spot method (average ROI size 0.15-0.19 mm 2 ), showing a 1.2-to 2-fold increase of MVD values in PC versus normal prostate [5,6,9,[28][29][30]. Recent large-scale TMA analyses of hot spots by Ebersdobler et al [5] also revealed 1.25-fold higher mean MVD in TMA spots with cancer versus non-cancerous tissue.…”
Section: Cd31 Mvd Counts Are Not Increased In Prostate Cancercontrasting
confidence: 88%
“…Most analyzed parameters were higher within normal glandular prostatic tissue (MVC, MVA, vessel lumen), whereas MVAF, vessel wall, and vessel perimeters were not significantly different. These findings using the large representative areas contradict most previously published data with the hot spot method (average ROI size 0.15-0.19 mm 2 ), showing a 1.2-to 2-fold increase of MVD values in PC versus normal prostate [5,6,9,[28][29][30]. Recent large-scale TMA analyses of hot spots by Ebersdobler et al [5] also revealed 1.25-fold higher mean MVD in TMA spots with cancer versus non-cancerous tissue.…”
Section: Cd31 Mvd Counts Are Not Increased In Prostate Cancercontrasting
confidence: 88%
“…Increased MVD has been shown to be associated with disease progression and metastasis in several cancers, including vulval, breast, and prostate cancers [2224]. A variety of endothelial cell markers have been used to identify microvessels for the purpose of counting.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] Studies have shown that MVD is higher in PCa than in benign prostate tissue. [19,20] Yeung et al [21] investigated the relation between MVD and PCa in vitro perfusion analyzed with micro-CT.…”
Section: Discussionmentioning
confidence: 99%